Plaque minerals in the prediction of caries activity - Pearce EIF, Dong Y-M, Yue L, Gao X-J, Purdie GL, Wang J-D. (Blackwell Synergy, 2002)
Background/Aims: Attempts to identify subjects who will develop caries lesions in future years have been only moderately successful, suggesting that one or more important risk factors are being overlooked. The aim of this study was to validate the use of plaque calcium, phosphate and fluoride concentrations as significant risk factors in caries.